Why Do Some T Cell Receptor Cytoplasmic Domains Associate with the Plasma Membrane? - van der Merwe, Philip Anton; Zhang, Hao; Cordoba, Shaun-Paul (Frontiers in Immunology, 2012)
Based on studies in model systems it has been proposed that the cytoplasmic domains of T cell receptor signalling subunits that have polybasic motifs associate with the plasma membrane, and that this regulates their phosphorylation. Recent experiments in more physiological systems have confirmed membrane association but raised questions as to its function.